Remote monitoring of the cardiac rhythm: where do we stand today?. Issue 4 (December 2016) - Deftereos, S.; Papoutsidakis, N.; Giannopoulos, G.; Kossyvakis, C.; Lekakis, J.
Abstract : Abstract: Remote monitoring systems, in their current forms, are networked communication solutions allowing exchange of digitized data from implanted or wearable devices. These data usually include electrocardiographic recordings, but nowadays they may encompass much more than that, allowing a continuously updated knowledge of a multitude of device‐ or patient‐related parameters. Remote monitoring has been shown, as one would have expected, to reduce the need for office visits and allow earlier detection—and thus management—of arrhythmic events. However, although there are hints that they may also be associated with improved clinical outcomes, the absence of randomized trials dictates a cautious interpretation of existing evidence. Furthermore, there are still several questions regarding their cost‐effectiveness, the patient populations that could benefit from them, as well as how the transmitted data should be interpreted and acted upon by physicians. In this review, we present and critically examine the current state of affairs of remote cardiac rhythm monitoring systems. Answer questions and earn CME :https://wileyhealthlearning.com/Activity2/4596216/Activity.aspx